IMPLEMENTASI KEBIJAKAN PEMBANGUNAN JALAN LINGKAR DURI-PINGGIR KABUPATEN BENGKALIS - Febri Surya Pratama; M. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The indicators of problems in the implementation of Duri-Pinggir ring road construction are as follows: The construction of Duri-Pinggir ring road has not been realized 100 percent even though it has entered the year 2015, AKuri Duri terminal becomes not functioning due to Duri-Pinggir Ring Road has not been realized, the number of inter-city bus And between provinces and trucks passing through urban areas causing congestion due to Duri-Pinggir ring road has not been realized. Problem formulation: how is the Implementation of Duri-Pinggir Bengkalis Road Roundabout Policy ?, what factors are the obstacles to the Implementation of Duri-Pinggir Range Road Policies Bengkalis Regency ?. Research Objective: to know the Implementation of Policy of Duri-Pinggir Ring Road Development of Bengkalis Regency, to know the factors that become obstacles of Implementation of Duri-Pinggir Road Development Policy of Bengkalis Regency. The data obtained in this research are analyzed descriptively qualitative. According to Edwards III (1980), the implementation of the policy is influenced by four variables, namely: Communication, in addition to the communities affected by the construction of Duri-Pinggir ring road, communication is also carried out by the local government of Bengkalis Regency with Bengkalis District House of Representatives. Resources, in the construction of Duri-Pinggir Bengkalis Ring Road is filled by experienced and qualified human resources. As for the finances of the Bengkalis Regency government and the Regional House of Representatives (DPRD) of Bengkalis Regency have included the construction of Duri-Pinggir ring road within Bengkalis District Budget (APBD) for fiscal year 2013, fiscal year 2014 and fiscal year 2015. Disposition, There is no problem that all involved have the desire to advance Bengkalis Regency, warm atmosphere, kinship, and complement each other happened in the discussion. The bureaucratic structure, in the preparation of the organizational structure, the filler of positions in the structure, the task of the structure filler must be in accordance with the legislation. Factors that hampered the implementation of Duri-Pinggir ring road policy of Bengkalis Regency: not yet obtained the permit from PT Chevron Pacific Indonesia, land acquisition.Keywords: implementation, policy